2022
DOI: 10.1002/adbi.202101310
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of ceRNA Networks in Frontal Cortex and Choroid Plexus of Brain during SARS‐CoV‐2 Infection Aggravates Neurological Manifestations: An Insight from Bulk and Single‐Cell Transcriptomic Analyses

Abstract: CSF) of patients with Parkinson's disease (PD) [5] and found to be potent in causing neurodegeneration by invading the neurons. [6] SARS-CoV-2 belongs to the family of these coronaviruses and it was also found to be neuro-invasive. [7] In addition to that, the cytokine storm due to SARS-CoV-2 infection is massively exhibited by a hyperinflammatory response. [8] The chronic neuroinflammation induced by cytokine storm is also being treated as a marker of neurodegenerative diseases like Alzheimer's (AD), PD, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 89 publications
(135 reference statements)
0
1
0
Order By: Relevance
“…Moreover, researches also demonstrated SARS-CoV-2 infection damaged the epithelium of choroid plexus and disrupted the blood-cerebrospinal fluid barrier in human brain organoids ( Pellegrini et al, 2020 ), ( Jacob et al, 2020 ), and the single-cell RNA sequencing study identified broad cellular perturbations and inflammation of choroid plexus in severe COVID-19 ( Yang et al, 2021 ). Besides, a recently published study also identified genes, as well as long non-coding RNAs that were dis-regulated in neurons of choroid plexus after SARS-CoV-2 infection ( Das and Podder, 2022 ). It was indicated that neurological complications of COVID-19 might arise more commonly due to aberrant inflammation throughout CNS, which might be relayed by the choroid plexus ( Thompson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, researches also demonstrated SARS-CoV-2 infection damaged the epithelium of choroid plexus and disrupted the blood-cerebrospinal fluid barrier in human brain organoids ( Pellegrini et al, 2020 ), ( Jacob et al, 2020 ), and the single-cell RNA sequencing study identified broad cellular perturbations and inflammation of choroid plexus in severe COVID-19 ( Yang et al, 2021 ). Besides, a recently published study also identified genes, as well as long non-coding RNAs that were dis-regulated in neurons of choroid plexus after SARS-CoV-2 infection ( Das and Podder, 2022 ). It was indicated that neurological complications of COVID-19 might arise more commonly due to aberrant inflammation throughout CNS, which might be relayed by the choroid plexus ( Thompson et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%